Approaches and Methods of Teaching English in Professional Classrooms (International Journal of Innovative Research in Engineering & Management, 2021)
In the last five decades, the value of English has grown to a new  height owing to the change in the mode of our business. The  globe has shrunken to a small village in which businesses are  carried out across different time zones and spaces in the virtual  world. In such a small world with multiple business networks,  English stands out as the most important lingua franca. The  language has achieved the stature of a world lingua franca as the  numbers of non-native speakers are growing in numbers. In such  context, English becomes an important language for the  professional students who aspire to become a successful  professional in his/her own right. Aligning with the need of the  students, the teachers and practitioners of English Language  Teaching, work tirelessly to meet the needs and requirements of  the students. This paper attempts to present the various  approaches and methodologies of teaching English to the  students of Engineering and Management in order to develop  their communication skills in English.
Keywords: Language Teaching; Approaches; Methodologies